Assessment of correlation of oxidative stress and insulin resistance with glucose-6-phosphate dehydrogenase activity in Type II diabetes mellitus patients - Beena Singh; Shweta Kumari (Wolters Kluwer Medknow Publications, 2021)
Background: The present study aimed to assess the correlation of oxidative stress glucose-6-phosphate dehydrogenase (G6PD) activity in type II diabetes mellitus (DM) patients. Methodology: Forty-eight type II DM patients and healthy subjects were recruited. In all, G6PD activity, protein carbonyl, and total thiol levels were measured. Results: The mean glycated hemoglobin (HbA1c) was 9.4% in Group I and 5.2% in Group II, G6PD activity was 6.5 U/gHb in Group I and 8.2 U/gHb in Group II, protein carbonyl was 14.2 nmol/mg protein in Group I and 3.5 nmol/mg protein in Group II, and total thiol level was 204.7 μmol/mL in Group I and 318.2 μmol/mL in Group II. In Group I, G6PD activity positively correlated with total thiol (r = 0.62) and negatively correlated with protein carbonyl (r = −0.73) and HbA1C (r = −0.67), protein carbonyl positively correlated with HbA1C (r =0.45) and negatively correlated with total thiol (r = −0.84), and total thiol negatively correlated with HbA1c (r = −0.30). Conclusion: G6PD may be considered a biomarker of oxidative stress and poor glycemic control in diabetic patients.